Designing learning material assisted by augmented reality to improve spatial thinking skills - Isharyadi, Ratri; Herman, Tatang (Al-Jabar: Jurnal Pendidikan Matematika, 2022)
Spatial thinking is a crucial ability to be mastered by students. On the other hand, the rapid development of technology in education, such as augmented reality (AR), is predicted to increase significantly in 2035. This technology should be utilized to provide new insights for students. However, the condition of learning resources related to AR currently needs to be improved. This study aims to design mathematics teaching materials on geometry materials using AR to improve spatial thinking skills. This study uses the Plomp model development research, which consists of three stages: preliminary, prototyping, and assessment. It is important to note that this paper reports results from preliminary. This article reports by collecting data through literature studies and questionnaires to mathematics teachers in the Rokan Hulu district. The findings reveal that the use of GeoGebra as an AR builder in Indonesia still needs to be created because of the excellent potential of Geogebra. AR learning resources on geometry at the high school level also need to be improved. Teachers agree that learning using technology has become necessary and are interested in using AR, especially in the geometry field. Based on the findings, we designed and developed Geogebra AR-assisted teaching materials based on these findings to improve spatial thinking skills.